Development, displacement and disparity: India in the last quarter of the twentieth century - Banerjee, Nirmala; Marjit, Sugata (New Delhi: Orient Longman, 2005)
This book is a collection of essays that tackle a crucial theme in developmental economics and planning. The essays: - look at the inequities and disparities of national resource distribution, and the need for a more equitable distribution of national developmental gains reflect a growing concern with many economic theorists over uneven regional development and the need for these issues to be looked at seriously, with a view to attend to them in the best possible ways are on the one hand a theoretical exposition of the economics of public goods supply, but on the other, they point to the lag between theoretical and academic understanding and practical initiative study the areas, evaluate the models of development and suggest new areas of research in development planning.
Inequality, deprivation and displacement -- The history and geography of regional development theory: a futile search for a paradigm -- Political institutions, distortions and regional disparities -- Political lobbying and discretionary finance in India: an aspect of regional political influence in a representative democracy -- Who should provide public goods? a perspective from the theory of organisations -- Notes towards a theory of industrialisation in the developing world -- Does the presence of surplus labour hinder production in Indian manufacturing? -- Infrastructure, income and regional economic development in India -- On the effects of trade in foodgrains -- Post-reforms export growth in India: an exploratory analysis
Includes bibliography and index
Keywords: Development Studies; Economics